Experience of heart transplantation with an extended cold ischemic time of donor heart - A. V. Fomichev; D. S. Khvan; H. A. Agaeva; M. O. Zhulkov; D. V. Doronin; A. M. Chernyavsky (Российский кардиологический журнал)
Aim. A retrospective analysis of the outcomes of heart transplantation (HT) with extended cold ischemic time of donor heart (more than 4 hours) versus heart transplantation with short cold ischemia time (less than 4 hours).Material and methods. The retrospective analysis included 52 recipients who underwent HT in the period from July 20, 2012 to October 23, 2019 in Meshalkin National Medical Research Center. The patients were divided into two groups: group 1 (n=26) — orthotopic HT with extended cold ischemic time (more than 240 minutes), group 2 (n=26) — short cold ischemia time (less than 240 minutes). The effect of cold ischemia duration on hospital survival, the function of donor heart, and the postoperative course was assessed.Results. A retrospective analysis revealed a higher rate of hospital survival in the group of recipients with extended cold ischemic time (more than 240 minutes) 88,5% compared to 80,7% in the second group. There was no difference between the groups in the acute rejection rate, the need for inotropic agents, mechanical circulatory support, and cardiac pacing, as well as the incidence of postoperative renal failure and infectious complications.Conclusion. Due to the small number of patients, our experience in HT with extended cold ischemic time does not allow us to draw global conclusions, but a preliminary comparison of HT with extended and short cold ischemic time did not reveal significant advantages in one group or another. This provides a basis for further accumulation of experience and research.